Factors that Influences Pedestrian Intention to Cross a Road While using Mobile Phone - Hanan, Suhaila Abdul; Said, Noor Fadhilah; Kamel, Aida Amelia Mohd; Amil, Siti Azwin Farhana Che (International Journal of Economics and Financial Issues, 2015)
Road accident has been identified as a cause of injury and death around the world including Malaysia. Among those who were killed and injured are pedestrian. There were few studies investigated the cause of the accident that involved the pedestrian in the other country. However, in Malaysia, as far as road safety and pedestrian is concerned, the research still at an early stage. The Theory of Planned Behavior (TPB) has been utilized widely in all research areas including road safety and pedestrian. Thus, this theory was used to understand the psychosocial factors that influence pedestrian intentional behavior. In particular, this paper examined the extent to which the Theory Planned Behaviour (TPB influenced pedestrian intention to cross a road while using mobile phone. This research utilized quantitative approach, that is a survey (n=107). The result indicated that subjective norm and perceived behavioral control (PBC) significantly influenced intention to cross a road when using mobile phone. Thus, based on the result, it was suggested that the safety awareness campaign and education should focus on subjective norm and perceived behavioral control e.g., Pedestrian Awareness Day. Keywords: Pedestrian; Intention; Safety; Road Crossing JEL Classifications: M000